EFFECT OF NIGELLA SATIVA SEEDâS OIL ON PHARMACOKINETICS AND PHARMACODYNAMICS OF GLICLAZIDE IN RATS - Adiwidjaja, Jeffry
Diabetes mellitus is a high prevalence metabolism disorder. WHO has reported that in 2005 200 millions people throughout the world suffered from diabetes. Previous studies showed an antihyperglycemic activity of N. sativa seed and its oils. The purpose of this research was to determine effect of N. sativa seed?s oil to bioavaibility of gliclazide when given concomitantly. Normal and insulin resistant male Wistar rats were divided into two groups (each n = 5). Rats were anesthethized by urethane 1.25 g/kg BW. The first group only received gliclazide 0.033 mg/g BW and the second group (n=5) received N.sativa seed?s oil 0.052 mg/g BW / day for 14 days prior to experimental day and 20 min prior to gliclazide administration on experimental day. Gliclazide and N.sativa seed?s oil were administered via intragastric. Blood samples were collected at 0; 0.25; 0.5; 0.75; 1; 1.5; 2; 3; 4; 8; 12; 18; 24 and 36 h after gliclazide administration. Gliclazide concentrations in plasma were determined by HPLC and its pharmacokinetic parameters were determined. Plasma glucose concentrations were measured by GOD-PAP method and AAC0-12 parameters were determined. N.sativa seed?s oil didn?t affect elimination and distribution phases of gliclazide significantly both in normal and insulin resistant rats. Significant increase of gliclazide bioavailability due to N.sativa seed?s oil administration was shown in normal and insulin resistant rats with the increase of 97% and 52%, respectively. N.sativa seed?s oil increased AAC0-12 of normal rats by 66%, while it didn?t affect AAC0-12 of insulin resistant rats significantly.